Culturally relevant schooling in Nunavut: Views of secondary school educators - Aylward, M.Lynn (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2009)
The Nunavut Department of Education is committed to creating culturally relevant Nunavut secondary schools using, as a foundation, the principles of Inuit Qaujimajatuqangit (Inuit traditional knowledge and learning), bilingualism, and inclusive schooling. This paper focuses on the voices of Nunavut secondary school educators by building upon the results of the Sivuniksamut Ilinniarniq research project, which explored multiple graduation options for Nunavut youth and was conducted by the Nunavut Department of Education in 2004. Some of the data for this research project came from a survey of secondary school educators. The open-ended responses revealed three main themes: the role of Inuit language and culture in Nunavut education; an increased role for family and community; and concerns about student engagement. An overview of the initial survey results as well as further qualitative analysis and discussion of the three main themes is provided. For current educational planning, it is necessary to understand how the majority non-Inuit secondary school educators view the Nunavut school system and the possible assumptions embedded within these views.